2006
DOI: 10.1093/pcp/pcl010
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Nitrate Uptake by Replacement of Asp105 by Asparagine in AtNRT3.1 in Arabidopsis thaliana L.

Abstract: An Arabidopsis mutant (rnc1) with a mutation at the 313th nucleotide from the translational start site of AtNRT3.1 was isolated. The mutation resulted in the replacement of aspartate by asparagine at the 105th amino acid in a region conserved among higher plants. In the rnc1 mutant, both the nitrate concentrations in plants and the nitrate uptake from the medium were <13% compared with those of the wild type, while AtNRT3.1 mRNA was accumulated similarly and both AtNRT1.1 and AtNRT2.1 mRNA were decreased. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…However, the region of NAR2 involving in interaction with NRT2 has not been clarified although the functional importance of aspartate residue in the central loop of NAR2 for HATS activity was suggested (Kawachi et al 2006). In this study, affinity-column binding analysis clearly showed that a direct protein-protein interaction occurred between the HvNRT2.1 C-terminal and the HvNAR2.3 central region.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…However, the region of NAR2 involving in interaction with NRT2 has not been clarified although the functional importance of aspartate residue in the central loop of NAR2 for HATS activity was suggested (Kawachi et al 2006). In this study, affinity-column binding analysis clearly showed that a direct protein-protein interaction occurred between the HvNRT2.1 C-terminal and the HvNAR2.3 central region.…”
mentioning
confidence: 73%
“…Indeed, there are several predicted phosphorylation sites (serine and threonine residues) in the C-terminus of HvNRT2.1 (Figure 1). On the other hand, in the rnc1 mutant of Arabidopsis, it has been shown that a conserved aspartate residue located in the central region of NAR2 protein is important for exhibiting HATS activity (Figure 1, Kawachi et al 2006). Therefore, the possibility of protein-protein interaction between HvNRT2 C-term and HvNAR2 cent was studied by affinity-column binding analysis.…”
Section: Immunological Detection Of Hvnrt2 and Hvnar2 Proteins In Memmentioning
confidence: 99%
“…This process was repeated once more using additional SNP markers SNP21.4 and SNP21.5, resulting in the mapping of the resistance locus to a 130-kb region. SNP analysis was performed as described previously (Kawachi et al, 2006). Primer information for the SSLP markers was obtained from the TAIR database (http://www.Arabidopsis.org/).…”
Section: Genetic Analysismentioning
confidence: 99%
“…The shaded letters indicate the amino acid residues conserved in at least four of the five sequences. The triangle indicates the aspartate residue shown to be essential for nitrate transport in A. thaliana (Kawachi et al 2006). Regulation of nitrate transport genes 487 (Trueman et al 1996), was conserved in the five PpNRT2 proteins, although the methionine residue was replaced with a leucine residue in the moss proteins.…”
Section: Characteristics Of the Deduced Ppnrt2 Proteinsmentioning
confidence: 99%